Series-connected renewable power generation - Wang, Gian Fatt (2012)
The time-varying photovoltaic (PV) power generation caused by the short fluctuation of irradiance and cloud cover result in power quality problems when the solar power is injected into the power grid. The intention of this project is to build a single phase series connected photovoltaic system with the Maximum Power Point Tracking (MPPT). It is a 230V, 50Hz grid to be connected in series. The power electronic converter system consists of a DC-DC voltage booster and a DC-AC single phase full bridge inverter. The devices are built with the gate signal generated and controlled by dSPACE CS1103 controller device, with the aid of MATLAB/Simulink.